What's the harm? Alcohol and marijuana use and perceived risks of unprotected sex among adolescents and young adults. (January 2018) - Dir, Allyson L.; Gilmore, Amanda K.; Moreland, Angela D.; Davidson, Tatiana M.; Borkman, April L.; Rheingold, Alyssa A.; Danielson, Carla Kmett
Abstract: The link between substance use and risky sexual behavior, particularly unprotected sex, among adolescents and young adults has been well established in the literature; however, less is known regarding how different patterns and types of substance use differentially relate to unprotected sex and perceived risks of unprotected sex. The current study examined perceived risks and unprotected sex among adolescents and young adults, and examined whether marijuana use, alcohol use, and dual marijuana and alcohol use were differentially linked to unprotected sex and perceived risks of unprotected sex. Method: A sample of N  = 144 adolescents and young adults (Mage = 18.77, SDage = 3.4, range: 12–25) completed self-report questionnaires regarding past month substance use, unprotected sex, and perceived risks of having unprotected sex. Results: In a hierarchical logistic regression, only alcohol use was related to having unprotected sex at last intercourse ( b  = 0.25, p  < 0.001). The second multinomial logistic regression showed that the interaction of alcohol and marijuana use was significantly related to lower levels of perceived risk of unprotected sex (moderate risk: b  = 0.06, p  = 0.04, OR = 1.07; no/slight risk: b  = 0.07, p  = 0.03). Conclusion: While dual marijuana and alcohol use was related to lower perceived risk of unprotected sex, only alcohol use only was associated with a higher likelihood of unprotected sex. Highlights: Significant association between dual alcohol/marijuana use and sexual risk perceptions. Alcohol use only was related to higher likelihood of unprotected sex. Unique relations between substance use pattern and perceived risk of vs. actual unprotected sex.